LEGAL PROTECTION AGAINST VICTIMS OF DOMESTIC VIOLENCE IN UNREGISTERED MARRIAGES - Nurdin, Muhammad Farid; Karim, Muhammad Said; Heryani, Wiwie (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
This study purposes to analyze Law No. 23 Year 2004 in providing legal protection to victims of domestic violence against marriages that are not registered at the Office of Religious Affairs. The research is normative-legal research, using the statute approach, conceptual approach, and case approach. The legal materials used are primary legal materials and secondary legal materials. The collected legal materials are then analyzed qualitatively. The results of the study indicate that the law affirms that every citizen has the right to obtain legal protection, including victims of domestic violence. Law No. 23 Year 2004 concerning the elimination of domestic violence was then present to provide legal certainty related to legal protection in the event of domestic violence, the violence is both physical and psychological violence, the government then makes regulations related to protection schemes if it occurs violence starts from the protection of the police, social services, and courts. Especially for unregistered marriages, they can still get legal protection based on Law No. 23 Year 2004 if it can be proven that it is true that a marriage has occurred and lives in the same household.